REVERSE TRANSCRIPTION POLYMERASE CHAIN REACTION-A REVIEW - Sri, K. Bhavya; Banu, Shaheen; Sumakanth, Mogili (Journal of Global Pharma Technology, 2024)
The reverse transcription polymerase chain response is straightforward, powerful, and exquisite innovation in the discipline of molecular biology. It helps in determining the gene expression and amplifying the gene of interest in numerous fields used to locate and quantify the quantity of a given DNA collection. It entails three steps: reverse transcription, PCR amplification, and electrophoresis. Among PCR, the maximum commonly used PCR technique is reverse transcription polymerase chain reaction abbreviated as RT-PCR. it is way utilized in molecular biology & genetic research that allows the detection & quantification of mRNA. in this, RNA template is first converted into a complementary DNA by use of a reverse transcriptase enzyme and is further used for exponential amplification the use of the PCR method. Many genes are recognized to have their own promoter regions that inform cells where to begin transcribing the unique gene. RT-PCR first starts by using the usage of reverse transcriptase enzyme to make DNA out of RNA that has been extracted from cells or tissue samples. The RNA is in the shape of a polymer. The opposite transcriptase copies the RNA into an open-ended DNA strand, preventing it when it encounters a unique non-coding location known as a